DEVELOPMENT OF THE SIELIN APPLICATION (INTEGRATED E-LEARNING SYSTEM) AS MEANS OF EDUCATIONAL MEDIA FOR DRUGS PREVENTION FOR TEENAGERS - M Ibni Rafif; Rifqi Zaidar Sahputra; Andi Aziz Farezky Lubis (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This research is motivated by the national drug emergency, where the prevalence of addictive substance use continues to rise rapidly and has begun to target students en masse due to weak supervision and monotonous conventional counseling techniques. The focus of this research problem is the development and testing of the effectiveness of the SIELIN (Integrated E-Learning Information System) application, focusing on empowering peers as the primary agents of drug prevention. Using a mixed-approach pre-post-test design, the research phase involved purposive sampling among high school students in South Sumatra Province, administering a pre-test, implementing an application intervention, and conducting focus group discussions and a post-test. Quantitative data were analyzed using descriptive statistics and factor analysis, while verbal data were processed through thematic analysis. The research findings indicate a significant increase in the average score for knowledge of the dangers of drugs, from 29.6 to 84.7, and in the indicator of self-rejection from 34.1 to 88.2. Quantitative factor analysis confirmed that the positive peer group variable was the most dominant element, with a factor loading of 0.86. The main research conclusion confirms that reforming the development strategy through a unified digital integration platform has proven highly effective in internalizing legal awareness to sustainably mitigate the risk of bias in adolescent promiscuity. ABSTRAK Penelitian ini dilatarbelakangi oleh status darurat narkoba nasional di mana angka prevalensi penggunaan zat adiktif terus meningkat pesat dan mulai menyasar lingkungan pelajar secara masif akibat lemahnya pengawasan serta teknik penyuluhan konvensional yang monoton. Fokus masalah riset ini diarahkan pada pengembangan dan pengujian efektivitas aplikasi SIELIN (Sistem Informasi E-Learning Terintegrasi) dengan memfokuskan sasaran pada pemberdayaan teman sebaya sebagai agen utama pencegahan narkotika. Menggunakan pendekatan campuran dengan desain pre-post test, tahapan penting penelitian dijalankan melalui seleksi sampel secara purposive sampling pada kalangan siswa menengah atas di Provinsi Sumatera Selatan, pemberian tes awal, intervensi penggunaan aplikasi, serta pelaksanaan diskusi kelompok terfokus dan tes akhir. Data kuantitatif dianalisis memanfaatkan statistik deskriptif dan analisis faktor, sedangkan data verbal diolah melalui analisis tematik. Temuan penelitian menunjukkan lonjakan skor rata-rata pengetahuan bahaya narkoba secara signifikan dari 29,6 menjadi 84,7 serta indikator sikap penolakan mandiri dari 34,1 menjadi 88,2. Analisis faktor kuantitatif mengonfirmasi bahwa variabel teman sebaya positif merupakan elemen paling dominan dengan nilai muatan faktor sebesar 0,86. Simpulan utama riset menegaskan bahwa reformasi strategi pembinaan melalui integrasi platform digital terpadu terbukti sangat efektif menginternalisasi kesadaran hukum demi memitigasi risiko bias pergaulan bebas remaja secara berkelanjutan.